2016
DOI: 10.1021/acsami.5b10975
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Electrical Properties of EOT HfO2 (<1 nm) Grown on InAs by Atomic Layer Deposition and Its Thermal Stability

Abstract: We report on changes in the structural, interfacial, and electrical characteristics of sub-1 nm equivalent oxide thickness (EOT) HfO2 grown on InAs by atomic layer deposition. When the HfO2 film was deposited on an InAs substrate at a temperature of 300 °C, the HfO2 was in an amorphous phase with an sharp interface, an EOT of 0.9 nm, and low preexisting interfacial defect states. During post deposition annealing (PDA) at 600 °C, the HfO2 was transformed from an amorphous to a single crystalline orthorhombic ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 37 publications
(72 reference statements)
1
14
0
Order By: Relevance
“…The difference in oxidation state of diffused In between the two samples can suggest another reaction process for In 2 O 3 related to the reactivity. Comparing the Gibbs free energy of HfO 2 (−1088.2 KJ/mol), Al 2 O 3 (−1582.3 KJ/mol), and In 2 O 3 (−830.7 KJ/mol), we conclude that the reaction of In with Al 2 O 3 or HfO 2 is not possible 6 . Therefore, the oxygen for the formation of In 2 O 3 can be externally supplied from the oxide surface.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…The difference in oxidation state of diffused In between the two samples can suggest another reaction process for In 2 O 3 related to the reactivity. Comparing the Gibbs free energy of HfO 2 (−1088.2 KJ/mol), Al 2 O 3 (−1582.3 KJ/mol), and In 2 O 3 (−830.7 KJ/mol), we conclude that the reaction of In with Al 2 O 3 or HfO 2 is not possible 6 . Therefore, the oxygen for the formation of In 2 O 3 can be externally supplied from the oxide surface.…”
Section: Resultsmentioning
confidence: 85%
“…In the case of the InAs substrate, As 2 O 3 and As 2 O 5 states were rarely detected in the as-grown HfO 2 /InAs, whereas elemental As and In 2 O 3 states were clearly measured by the result of interfacial reactions between interdiffused oxygen and the InAs substrate. During the post-deposition annealing process at 600 °C, oxidation states of As 2 O 3 , As 2 O 5 , and In 2 O 3 were generated at the surface region of the HfO 2 6 . In the case of GaSb, the Ga–O and Ga 2 O 3 states were generated on the GaSb surface during the ALD process even at 250 °C 11 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of interface state desnity up to a factor of 40 by passivation of InAs surfaces by a HfO 2 overlayer has been reported . However, we cannot rule out an alternate explanation based on compensating acceptor states introduced by HfO 2 . ,, …”
mentioning
confidence: 76%
“…Past research has shown that indium (In) can inject into HfO 2 due to high temperature or an electric field . In this article, based on this result, In is used as the top electrode, and the electric field is used to drive In into the switching layer.…”
mentioning
confidence: 99%